Effects of individualised training zones and adaptations in elite female rowers - Tomescu, V.; Teodorescu, S. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2018)
Through this paper, we want to prove that the contribution of specific aerobic exercise can be improved in order to increase the total exercise capacity through physiological adaptations. We conducted a cross-sectional observational study on a group made up of 19 elite female rowers between the months of April and November 2015, in Brasov and Bucharest cities, Romania. Two VO2max tests were carried out in the mentioned period. The first test was initiated during the pre-competitive season 2014-2015, while the second test was performed during the general training period 2015-2016. The functional cardiovascular and respiratory parameters were studied, indicating the athlete`s progress and the energy metabolism adaptation. After processing the data relating to the VO2max tests, the following conclusions were drawn: the total increase in lower aerobic effort and higher aerobic effort was significantly higher than the effort performed during the 2014-2015 competitive season. This aspect, through data monitoring, associated increased lung capacity validated through the following monitored parameters: VE/VO2, VE/VCO2 and VT, VO2, respectively, establishing their direct influence on the reported progress and the performance achieved by the athletes during the specific maximal effort. The proportion of VO2/kg was associated with the development and value of the ventilatory thresholds determining their influence on the evolution of the athlete within a maximal effort.